Principles and Practice of Constraint Programming – CP 2007
DOI: 10.1007/978-3-540-74970-7_35
|View full text |Cite
|
Sign up to set email alerts
|

Towards Robust CNF Encodings of Cardinality Constraints

Abstract: Abstract. Motivated by the performance improvements made to SAT solvers in recent years, a number of different encodings of constraints into SAT have been proposed. Concrete examples are the different SAT encodings for ≤ 1 (x1, . . . , xn) constraints. The most widely used encoding is known as the pairwise encoding, which is quadratic in the number of variables in the constraint. Alternative encodings are in general linear, and require using additional auxiliary variables. In most settings, the pairwise encodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…In current implementations, auxiliary variables are not handled differently by SAT solvers. However, the special handling of these variables may be considered in the future, as it has been recently shown that not branching on these variables, as well as not learning constraints with these variables, leads in general to more robust performances [15]. Besides the basic model outlined above, SAT-based haplotyping requires the inclusion of a number of effective techniques, including lower bounds and identification of symmetries [11] (see Section 4.3).…”
Section: Figure 3 Boolean Variables Used In Shipsmentioning
confidence: 99%
“…In current implementations, auxiliary variables are not handled differently by SAT solvers. However, the special handling of these variables may be considered in the future, as it has been recently shown that not branching on these variables, as well as not learning constraints with these variables, leads in general to more robust performances [15]. Besides the basic model outlined above, SAT-based haplotyping requires the inclusion of a number of effective techniques, including lower bounds and identification of symmetries [11] (see Section 4.3).…”
Section: Figure 3 Boolean Variables Used In Shipsmentioning
confidence: 99%
“…Encodings using auxiliary variables are mainly useful for constraints on a large number of input variables, when the full prime representation is too large. Moreover, the experimental results in [19] suggest that a SAT solver can be modified to minimize the disadvantage of introducing auxiliary variables. Another experimental evaluation of various cardinality constraints and their encodings appears in [15].…”
Section: Introductionmentioning
confidence: 99%
“…We add to the important and growing literature on modelling of constraints in SAT [6]. Most study has been devoted to constraints such as linear constraints including the special case of cardinality constraints [1,2,8,24].…”
Section: Introductionmentioning
confidence: 99%